Impacts of nitrogen application on forage grasses to maize in no-tillage sytem - Marques, Letusa Momesso [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
The success of no-tillage system depends on the knowledge of the agricultural system as a whole. The use of grass Urochloa sp. as cover crop in agriculture results in slow organic material decomposition due to high biomass production and changes in soil microbe, in particular in biological processes related to nitrogen (N). Because N is a nutrient present in the main biochemical reactions in plants and microorganisms, N management requires special attention. Therefore, this research aimed to improve N-use efficiency from both agronomic and biological perspectives. The main objectives were to (i) assess the impact of N fertilizer and forage species on maize in the NT system, and (ii) determine the interactions between microbes x N x environmental factors. A field experiment was evaluated, in which palisade grass (Urochloa brizantha) and ruzigrass (U. ruziziensis) grown with four N management, included: (i) control zero-N (no N application), (ii) N applied on green cover crops at 35 days before maize seeding (35 DBS), (iii) N applied on cover crop residues at 1 day before maize seeding (1 DBS), and (iv) conventional method of N applied at sidedressing in maize growth), at a rate of 120 kg N ha-1 as ammonium sulfate. The hypothesis of Chapter 1 that N applied on alive cover crops or cover crop residues could replace N-sidedressing application (conventional method) for maize was confirmed when: (a) N was applied on palisade grass at 35 DBS or its residues at 1 DBS, and (b) N was applied on ruzigrass residues at 1 DBS. Due to results of first chapter, another experiment was conducted with the objective of assessing whether either the early N application on alive cover crops or on cover crop residues or the conventional method of N application contributed to the recovery of total-N and fertilizer 15N by maize, by cover crop residues, and in the soil over growing season. Although the hypothesis that N applied on palisade grass to achieve high grain yields of maize was previously confirmed, the results Chapter 2 showed that the best option is applying nitrogen fertilizer as the current fertilizer recommended method (40 kg N ha-1 at maize seeding plus 120 kg N ha-1 sidedressed in V6 growth stage) for enhance grain yields of maize and N recovery from fertilizer.
Impactos da adubação nitrogenada em gramíneas forrageiras para cultivo do milho em sistema de semeadura direta
Keywords: Brachiaria spp.; Zea mays L.; crop residues; Nitrogen uptake efficiency; Tropical agriculture